2003
DOI: 10.1016/s1083-8791(03)00099-5
|View full text |Cite
|
Sign up to set email alerts
|

High-dose myeloablative therapy and autologous peripheral blood progenitor cell transplantation for elderly patients (greater than 65 years of age) with relapsed large cell lymphoma

Abstract: Eleven elderly patients (older than 65 years) with relapsed large cell lymphoma were treated with high-dose myeloablative therapy and autologous peripheral blood progenitor cell support (ABMT). All 11 patients were in sensitive relapse at the time of ABMT. Treatment-related mortality was 9%. Median CD34 cell collection was 4.8 x 10(6) cells/kg. Median time to hematologic recovery was 11 days for granulocytes (range, 9 to 16 days) and 18 days for platelets (range, 14 to 42 days). Nine of 11 patients (81%) achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…There are no conclusive data to recommend one conditioning regimen over another in this population. [7][8][9]26 We have demonstrated that a modified BU and CY regimen in selected patients X60 years of age is well tolerated. The dose of BU has been reduced to 14 doses of 0.8 mg/kg i.v.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…There are no conclusive data to recommend one conditioning regimen over another in this population. [7][8][9]26 We have demonstrated that a modified BU and CY regimen in selected patients X60 years of age is well tolerated. The dose of BU has been reduced to 14 doses of 0.8 mg/kg i.v.…”
Section: Discussionmentioning
confidence: 91%
“…The 100-day transplant-related mortality was 9%. 9 The Mayo clinic series reported an event-free survival of 38% in 93 patients, 60-76 years old, who received SCT for NHL after conditioning with BEAC or BEAM. Transplant-related mortality was 5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous reports as well as data obtained from other transplant centers confirm that procedure-related toxicity and mortality may be reduced by using nonmyeloablative or reduced intensity conditioning prior to transplantation of allogeneic stem cells, while retaining the antitumor effects of alloreactive donor lymphocytes. 5,6,[8][9][10] Nevertheless, data regarding SCTrelated toxicity in elderly patients are scarce and focus more concentrated on autologous [11][12][13][14][15] than allogeneic SCT. 10,[16][17][18] In this report, we present our cumulative experience in elderly patients (X60 years) undergoing allogeneic SCT with RIC for hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%